EXPERIENCE REPORT: QUALITY OF LIFE OF HEALTHCARE RESIDENTS - Conceição Gomes Lima, Andréa; Lima Barros, Vanessa; Ramos da Silva de Oliveira, Vivien (Health and Society, 2023)
During the postgraduate course in Trauma-Orthopedic Physiotherapy with an emphasis on Manual Therapy at the State University of Piauí, there was an awakening of interest focused on the residents’ quality of life, aiming to diagnose how they feel about the workload , considering the effects of work overload on the quality of their lives. Therefore, this study aims to report the quality of life of residents in Family Health at the Faculty of Medical Sciences (FACIME) of the Health Sciences Center (CCS) at UESPI. Therefore, the present study is an experience report, being carried out between April and May 2023 with a group of 11 health residents from the following areas of training: Physiotherapy, Nursing, Physical Education, Dentistry, Nutrition, Service Social and Psychology. Conversation circles were held, which focused on aspects such as health status; Presence of chronic illness; Relationship between age and weight; Practice of physical exercise; The reasons considered by them related to physical inactivity; The average time spent on physical activity performed; Level of physical activity; Place for daily meals; The occurrence of absence from work in the last 12 months; Relationship between food and weight; Stress level; and the reasons for the occurrence of stress. Therefore, through the observations carried out, it was possible to conclude that despite being health professionals, residents are very tired and have several complaints related to physical and mental health, due to the extensive working hours. This information goes back to the need to plan greater attention to these professionals and their training process, demanding the implementation of actions aimed at well-being and reducing stressful situations.